On record : popular Afrikaans music & society : 1900-2017 - Van der Merwe, S. D. (SUN MeDIA, 2017)
"Investigates the interplay between popular music and the unfolding of Afrikaans culture politics from the start of the twentieth century to the present. It includes a search for the earliest recorded Afrikaans songs and documents subsequent phases of music development that reflect the agency of ordinary individuals - artists and listeners - against a background of fundamental societal and political change. Regards both the music mainstream and the alternative, and reveals, among other things, historical cases of compliance and resistance regarding the master narrative of Afrikaner nationalist ideology, the attempts by cultural entrepreneurs to establish authority over popular Afrikaans culture, class tension, lasting racial exclusivity, protest and censorship "--